A companion to the philosophy of time - Dyke, Heather; Bardon, Adrian (Malden, MA : J. Wiley, 2013)
A Companion to the Philosophy of Time presents the broadest treatment of this subject yet; 32 specially commissioned articles - written by an international line-up of experts - provide an unparalleled reference work for students and specialists alike in this exciting field. The most comprehensive reference work on the philosophy of time currently availableThe first collection to tackle the historical development of the philosophy of time in addition to covering contemporary workProvides a tripartite approach in its organization, covering history of the ph.
pt. 1. The history of the philosophy of time -- pt. 2. Time as a feature of the physical world -- pt. 3. Time as a feature of human experience.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Time; Time; PHILOSOPHY -- Metaphysics; Time; Electronic books